Distal-less homeobox genes Dlx5/6 regulate Müllerian duct regression - Mullen, Rachel D.; Bellessort, Brice; Levi, Giovanni; Behringer, Richard R. (Frontiers in Endocrinology, 2022)
Dlx5 and Dlx6 encode distal-less homeodomain transcription factors that are present in the genome as a linked pair at a single locus. Dlx5 and Dlx6 have redundant roles in craniofacial, skeletal, and uterine development. Previously, we performed a transcriptome comparison for anti-Müllerian hormone (AMH)-induced genes expressed in the Müllerian duct mesenchyme of male and female mouse embryos. In that study, we found that Dlx5 transcripts were nearly seven-fold higher in males compared to females and Dlx6 transcripts were found only in males, suggesting they may be AMH-induced genes. Therefore, we investigated the role of Dlx5 and Dlx6 during AMH-induced Müllerian duct regression. We found that Dlx5 was detected in the male Müllerian duct mesenchyme from E14.5 to E16.5. In contrast, in female embryos Dlx5 was detected in the Müllerian duct epithelium. Dlx6 expression in Müllerian duct mesenchyme was restricted to males. Dlx6 expression was not detected in female Müllerian duct mesenchyme or epithelium. Genetic experiments showed that AMH signaling is necessary for Dlx5 and Dlx6 expression. Müllerian duct regression was variable in Dlx5 homozygous mutant males at E16.5, ranging from regression like controls to a block in Müllerian duct regression. In E16.5 Dlx6 homozygous mutants, Müllerian duct tissue persisted primarily in the region adjacent to the testes. In Dlx5-6 double homozygous mutant males Müllerian duct regression was also found to be incomplete but more severe than either single mutant. These studies suggest that Dlx5 and Dlx6 act redundantly to mediate AMH-induced Müllerian duct regression during male differentiation.